2013
DOI: 10.4236/oja.2013.33a007
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Propagation of Ultrasonic Waves in Piezoelectric Graphene Nanoribbon

Abstract: Generation and propagation of ultrasonic waves in single layer Graphene Nanoribbon is studied using semi-classical approach. When piezoelectric Graphene Nanoribbon (GNR) is exposed to time varying light beam, ultrasonic waves are produced which propagate in the medium. At low frequencies, we observed oscillations of the ultrasonic observables, velocity change and attenuation which are characteristics of massless Dirac fermions in graphene. Exploiting this oscillatory behavior, we estimate graphene's electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The acoustic behavior of G/PVA MBs does not change with respect to the plain PVA MBs (see Figure S10 in the Supporting Information), indicating that the anchored graphene does not affect the intrinsic echogenic properties of microbubbles shell. To date, few studies have investigated the acoustic properties of graphene, where it was reported a strong emission of ultrasonic waves in the range of THz frequencies . However, Chivikula et al have demonstrated that surface acoustic waves in graphene may occur at lower frequencies (MHz) in response to optical irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic behavior of G/PVA MBs does not change with respect to the plain PVA MBs (see Figure S10 in the Supporting Information), indicating that the anchored graphene does not affect the intrinsic echogenic properties of microbubbles shell. To date, few studies have investigated the acoustic properties of graphene, where it was reported a strong emission of ultrasonic waves in the range of THz frequencies . However, Chivikula et al have demonstrated that surface acoustic waves in graphene may occur at lower frequencies (MHz) in response to optical irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To date, few studies have investigated the acoustic properties of graphene, where it was reported a strong emission of ultrasonic waves in the range of THz frequencies. 57 However, Chivikula et al have demonstrated that surface acoustic waves in graphene may occur at lower frequencies (MHz) in response to optical irradiation. This effect results from the conversion of the optical energy, absorbed by the graphene flake, to the heating of the sample.…”
Section: Field Emission Scanning Electron Microscopy (Fesem)mentioning
confidence: 99%
“…Among piezoelectric materials, polyvinylidene fluoride (PVDF) is a well-known piezoelectric polymer [3]. This piezoelectric polymer can generate ultrasonic flexural waves because of its flexibility and piezoelectric properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Azizyan [43] calculated the absorption coefficient in a quantized electric field. Furthermore, Acoustic wave absorption/amplification in Graphenes [44,45,46], Cylindrical quantum wires [47] , and quantum dots [48,49] have all received attention. On the concept of Acoustoelectric effect (AE) in bulk [50] and low-dimensional materials [51], much research has been comprehensively done both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%